Difficult and failed intubation management in obstetrics. Issue 8 (August 2022) - Elsayed, Eslam; Clayton, Rhys
Abstract: Failed intubation in obstetrics remains a topical issue, a rare but potentially devastating complication of obstetric general anaesthesia. The 2015 guidelines produced following several years of collaborative work between the Difficult Airway Society (DAS) and Obstetric Anaesthetists' Association (OAA) remain the definitive text. While deaths from failed intubation have declined significantly over 30 years, the incidence of failed intubation remains fairly constant at 1:300, with the latest studies showing a rate of 1:224. This reflects the significant decline in the use of general anaesthesia for caesarean section over the last three decades; however, it also highlights a decreased exposure for trainees to tracheal intubation in the obstetric population.